2020
DOI: 10.1212/wnl.0000000000010372
|View full text |Cite
|
Sign up to set email alerts
|

Ocular motor measures of visual processing changes in visual snow syndrome

Abstract: Objective:To determine whether changes to cortical processing of visual information can be objectively evaluated using three simple ocular motor tasks to measure performance in patients with visual snow syndrome (VSS).Methods:Sixty four patients with VSS (32 with migraine and 32 with no migraine), and 23 controls participated. Three ocular motor tasks were included: prosaccade (PS), antisaccade (AS), and interleaved antisaccade-prosaccade (AS-PS) tasks. All these tasks have been used extensively in both neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…We have previously demonstrated VSS-specific alterations to visual processing that are consistent with stronger attentional capture (8,9). We propose that the corresponding imbalance between saccade facilitation and inhibition results in an increased number of erroneous saccades and shorter saccade latencies.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We have previously demonstrated VSS-specific alterations to visual processing that are consistent with stronger attentional capture (8,9). We propose that the corresponding imbalance between saccade facilitation and inhibition results in an increased number of erroneous saccades and shorter saccade latencies.…”
Section: Discussionmentioning
confidence: 51%
“…With the aim to provide objective evidence of neuropathological changes in VSS, our previous studies have investigated visual processing performance in VSS individuals using highly sensitive ocular motor (OM) tasks (8,9). The first of these studies (8) demonstrated that participants with VSS generated faster eye movements toward suddenly appearing visual stimuli and failed more often to inhibit erroneous eye movements to stimuli not consistent with task demands. We also showed that this occurred irrespective of the complexity of the task presented.…”
Section: Introductionmentioning
confidence: 99%
“…Solly et al utilized oculomotor tasks to examine 64 VSS patients and 23 controls (one subgroup of VSS patients with migraine, one without migraine, and a healthy control group). They demonstrated significantly quicker prosaccades in VSS patients as well as more errors in incongruencies between precue and target ( 37 ). A follow-up study with 67 patients examined interfering or conflicting saccade tasks (of which one was internally cued) again showing quicker prosaccadic movements and more errors in choosing (also internally cued) antisaccadic (contralateral) marks.…”
Section: Resultsmentioning
confidence: 99%
“…Mehta et al reported that 7.1% of their cohort with VS had a diagnosis of fibromyalgia ( 16 ). Additionally, postural orthostatic tachycardia syndrome ( 16 ), dizziness ( 16 ), balance problems ( 15 ), paresthesia ( 37 ), and tremor ( 15 ) have been described, but the latter without a further differentiation of the subtype.…”
Section: Resultsmentioning
confidence: 99%
“…VSS often presents with a number of comorbidities, most commonly migraine and tinnitus (2,4), but also other sensory symptoms, including paraesthesia and dizziness (5,6). Notably, a range of psychiatric symptoms are consistently reported in VSS patients; these include depression and anxiety, (2,3,5), as well as fatigue, sleep disturbances (7,8), and depersonalisation, a dissociative experience involving a sense of estrangement from the body (9).…”
Section: Introductionmentioning
confidence: 99%